1944
DOI: 10.1111/j.1744-7348.1944.tb06225.x
|View full text |Cite
|
Sign up to set email alerts
|

Inert dust insecticides: Part I. Mechanism of action

Abstract: The mode of action of inert dust insecticides on the grain weevil (Calandm p a -L.) has been investigated by determination of mortality-time curves and by a detailed study of the influence of dusts on the water relations of the insects. It has been found that dusts do not depend for heir action on MY chemical reactivity, some highly inert substances such as diamond and carborndurn being very effective. A physical process is therefore indicated.Dusts do not penetrate into the respiratory system, and although la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Alexander et al [13] showed that the mode of action for inert dust insecticides was independent of chemical reactivity. We have previously shown that concrobium dust causes mortality in Reticulitermes flavipes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Alexander et al [13] showed that the mode of action for inert dust insecticides was independent of chemical reactivity. We have previously shown that concrobium dust causes mortality in Reticulitermes flavipes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mineral particles have been studied for insecticide action (Alexander et al 1944;David and Gardiner 1950) and for effects on fungal infection (Farmer 1993). New forms of hydrophobic mineral particles were discovered to deter feeding of fruit-damaging insects such as pear psylla (Cacopsylla pyricola Foerster) (Glenn et al 1999;Puterka et al 2000).…”
Section: Mots Clésmentioning
confidence: 99%
“…Insect mortality is induced primarily as a result of water loss (1) (Alexander et al, 1944a(Alexander et al, , 1944b) and absorption of waxy layer from insect's cuticle (silica gels and diatomaceous earth containing amorphous silicon dioxide). Other possible causes are blocking the spiracles and causing insects to die from asphyxiation and ingestion of the dust particles causing the gut destruction (Ebeling, 1971;Maceljski and Korunic, 1972;Le Patourel, 1986).…”
Section: Introductionmentioning
confidence: 99%